Escherichia coli from biopsies differ in virulence genes between patients with colorectal neoplasia and healthy controls - Bosák, Juraj; Kohoutová, Darina; Hrala, Matěj; Křenová, Jitka; Morávková, Paula; Rejchrt, Stanislav; Bureš, Jan; Šmajs, David (Frontiers in Microbiology, 2023)
Pathogenic strains of Escherichia coli have been clearly identified as the causative agents of extraintestinal and diarrheal infections; however, the etiopathogenic role of E. coli in other conditions, including colorectal cancer, remains unclear. This study aimed to characterize mucosal E. coli isolates (n = 246) from neoplasia patients and healthy controls for the presence of 35 genetic determinants encoding known virulence factors. Virulence determinants encoding invasin (ibeA), siderophore receptor (iroN), S-fimbriae (sfa), and genotoxin (usp) were more prevalent among E. coli isolated from patients with neoplasia compared to the control group (p < 0.05). In addition, the prevalence of these virulence determinants was increased in more advanced neoplasia stages (padj < 0.0125). Compared to patients with advanced colorectal adenoma and carcinoma, the ibeA gene was rarely found in the control group and among patients with non-advanced adenoma (p < 0.05), indicating its potential as the advanced-neoplasia biomarker. Patients with neoplasia frequently had E. coli strains with at least one of the abovementioned virulence factors, whereby specific combinations of these virulence factors were found. These findings suggest that E. coli strains isolated from patients with colorectal neoplasia possess several virulence factors, which could contribute to the development of neoplastic processes in the large intestine.